(3eLjH GdfOG Edi TQM bWQ GdfOGs - (3GdaGcgj Gdecj, LeGd GdOjf, YHO Gddg Hf CMeO Hf YHO Gddg Hf CMeO Hf Ydj, (B972 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdQGaY ef GfNaVCeG HYO agPG TQM dWja hVYJg Ydi GdebOeI GdehVhYI aj Yde GdYQHjI GdeSeGI HbWQ GdfOG hHd GdUOG ddEeGe GHf gTGe GdCfUGQjhSejJg eLjH GdfOG Edi TQM bWQ GdfOGs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3WHb GdehUhd Cj eWGHb dg aj GdEaQGO hGdJPcjQ haQhYgG djQHWgG Hgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 69s
(3eYLe GdeDdajf(B: 2 / 266s
(3cTa GdXfhf(B: 2 / 1352s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs